Folk costumes in the photographs by Julije Kempf and Atelier Wollner at the beginning of the 20th century - Matoković, Dubravka (Array, 2020)
Photographs from the first two decades of the 20th century, taken by Julije Kempf, the founder of City museum Požega and the photography atelier named Atelier Wollner in Požega, proved a useful documentary source for the studies of traditional dress in rural Požega area from the end of the 19th and the beginning of the 20th century. A large number of their photographs is preserved in the Collection of Photographs and Negatives in City museum Požega. These photographs provide a historical overview of men’s and women’s folk costumes from the end of the 19th and the first two decades of the 20th century, showing the appearance, the changes and fashion influences in traditional folk costumes in the villages near Požega.